Pemanfaatan Ekstrak Gel Lidah Buaya (Aloe Vera) Terhadap Bakteri Propionibacterium Acnes - Suci Fabilla; Ardi Mustakim (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
The aim of this study was to test the effectiveness of aloe vera gel extract (Aloe Vera) against the Propinibacterium acnes bacteria, which is the main cause of acne on human skin. Aloe vera is known by the scientific name Aloe Vera L. and has long been used by people as an ingredient in cosmetics, skin care, wound healing and hair fertilizer. The methods used in this literature review include sampling aloe vera gel extract, testing antibacterial activity against Propionibacterium acnes bacteria, and data analysis to determine the effectiveness of the extract. Although there are differences in testing methods and concentrations used, most studies show this extract is effective in inhibiting Propionibacterium acnes bacteria. The conclusion of this review provides a safer alternative for treating acne using herbal products compared to using antibiotics.